Pengembangan Strategi Pemasaran pada UMKM Kuliner di Kabupaten Sleman - Lukas Kopong Tukan; Ratri Paramitalaksmi (Institut Teknologi dan Bisnis Semarang, 2023)
Limited promotional media means that marketing and sales methods are still small in scope so that MSMEs cannot manage their businesses effectively and often experience delays in their development. This Community Service aims to help simplify the marketing process for culinary MSMEs, namely Siomay Indul and Warung Makan